Congo Red Adsorption Capacity of Lignocellulosic Biomass by Sodium Hydroxide Treatment - Li, Hui-Xing; Zhang, Rui-Jing; Tang, Lei; Zhang, Jian-Hua; Mao, Zhong-Gui (Asian Journal of Chemistry, 2015)
To investigate the enhancement of Congo red adsorption capacity of lignocellulosic biomass with sodium hydroxide treatment, five various lignocellulosic biomasses were employed and respectively treated by different concentration of NaOH to remove congo red from aqueous solution. Results showed that NaOH treatment is an effective method for enhancement of congo red adsorption capacity of the biomasses. The capacity of sorghum stalk was the most considerably enhanced by NaOH treatment in comparison to that of other biomasses. Fourier transform infrared spectroscopy showed that the C=O bond of carboxylic acid or its ester in biomasses was destroyed and the -OH and -NH bonds in biomasses were varied by NaOH treatment. Scanning electron microscopy demonstrated that structure of the biomasses was breakdown after NaOH treatment. It is deduced that NaOH treatment considerably enhanced the congo red adsorption capacity of lignocellulosic biomass is due to destruction of its structure and variation of its functional groups.